PENGGUNAAN TEKNOLOGI INFORMASI DALAM PENDIDIKAN - Fenny Purwani (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2013)
The development of information communication technology (ICT) or Information and Communication Technology (ICT) is increasingly more active over the last two decades and has created a change in many ways, including in education. Information technology is a combination of computer technology, databases, networks and improved communications, and Information Management Personnel. The aplication of ICT in teaching and learning can be use to make learning media (CAI), e-Learning, Virtual Library, the Virtual School and the Virtual University